CMOS-MEMS Thermal-Piezoresistive Resonators and Oscillators for Sensors - Zope, Anurag; Li, Sheng-Shian (Frontiers in Mechanical Engineering, 2022)
Microelectromechanical systems (MEMS) have seen widespread commercial use due to their compact size, high performance, and low cost. MEMS resonators have emerged as front runners for sensing (accelerometers, gyroscopes, particulate matter, etc.) and frequency (RF front-end, filters, timing, and frequency source) applications. The excellent stability, resolution, and accuracy of resonators lend them to be an ideal candidate to implement sensors. CMOS-MEMS technology allows for rapid, large-scale, and low-cost manufacturing. Thermal-piezoresistive resonators (TPR) are promising candidates due to their favorable potential with scaling and robust performance in the ambient environment. A detailed finite element method (FEM) simulation flow is presented along with a mathematical model for device optimization. The devices were fabricated with commercial CMOS technology utilizing the front-end-of-line (FEOL) polysilicon and back-end-of-line materials like silicon-dioxide and interconnect metal. The flexibility of selective material placement in layout and complex routing using multi-metal interconnect is employed to develop a balanced TPR design at 2 MHz. A 5-MHz bulk mode TPR was designed for mass sensing application. The fabricated devices were characterized and their performance is compared with other state-of-art works. Finally, the developed devices were used in real-world applications for mass sensing and pressure sensing. The device achieved mass sensitivity of 25 kHz/ng. The TPR devices combine principles of Pirani gauge and resonant sensors for improving sensing range from 2 Torr to 760 Torr (1 atm).